Development of Interactive E-Module on Learning IPAS - Yunita Susanti; Suci Islami; Windy Widya Kusuma Ningrum; Asep Nuryadin; Muhammad Aizuddin bin Ab Alim (LPPM Universitas Terbuka, 2023)
This research aims to develop an interactive e-module as an additional learning media for fourth-grade elementary schools in the Natural and Social Sciences subject (IPAS). The study was conducted utilizing the ADDIE approach of research and development. Fourth-grade students and instructors at SDN Cikadongdong verified the product before it was released. Observation, interviews, and questionnaires were used as the primary methods of data collection. The results of product trials based on the teacher’s response showed a score of 95.8%, which was in the very good category. In addition, students’ responses based on interview results showed that the students liked the interactive e-module because the appearance of the interactive e-module was attractive, not boring, and easy to use. Thus, it can be concluded that the interactive e-module is considered a very good category and is suitable to use as an additional learning medium in fourth-grade Natural and Social Sciences learning.